On thermionic emission from plasma-facing components in tokamak-relevant conditions. (14th July 2017) - Komm, M; Ratynskaia, S; Tolias, P; Cavalier, J; Dejarnac, R; Gunn, J P; Podolnik, A
Abstract: The first results of particle-in-cell simulations of the electrostatic sheath and magnetic pre-sheath of thermionically emitting planar tungsten surfaces in fusion plasmas are presented. Plasma conditions during edge localized modes (ELMs) and during inter-ELM periods have been considered for various inclinations of the magnetic field and for selected surface temperatures. All runs have been performed under two assumptions for the sheath potential drop; fixed or floating. The primary focus lies on the evaluation of the escaping thermionic current and the quantification of the suppression due to the combined effects of space-charge and Larmor gyration. When applicable, the results are compared with the predictions of analytical models. The heat balance in the presence of thermionic emission as well as the contribution of the escaping thermionic current to surface cooling are also investigated. Regimes are identified where emission needs to be considered in the energy budget.